PENERAPAN SISTEM DAN PROSEDUR UANG PERSEDIAAN PADA BADAN PERENCANAAN PENELITIAN DAN PENGEMBANGAN KABUPATEN MINAHASA SELATAN - Rahayu, Magfirah S.; Manossoh, Hendrik; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2017)
Public estimate is a planning tool as well as local financial control, the execution of expenditure by local government to do an activity must be accounted by PPTK (Activity Technical Management Officer) on a timely basis. Fundamentally, Money Inventory (MI) can only be provided to finance the operational payment needs of the work unit, in the process of absorption of APBD, fund cash disbursement used is a Money Inventory (MI) accounting system in the form of Replace Money (RM), This study aims to evaluate the implementation of System and Inventory Money Prosedur at the planning, Reasearch and Development Agency of South Minahasa Regency throught descriptive analysis method collected by means ofÂ observation and interview. Based on the results of research implementation of system and money inventory procedures has been done effective way means it has been done effective way means it has been in accordance with the theory of accounting system and existing rules include related functions and documents used.Keywords: Procedure, Money Inventory, Replace Money